Early Concrete Structures: Patented Systems and Construction Features. Issue 3 (3rd April 2018) - Marcos, Ignacio; San-José, Jose-Tomas; Santamaría, Amaia; Garmendia, Leire
ABSTRACT: Reinforced concrete structures came to Spain in the late-19th century, somewhat after the development of this new construction material elsewhere in Europe. Their introduction was pioneered in industrialized areas, especially Northern Spain, under systems first patented in other European countries. Local constructors built structures under patents with little or no explanations to account for calculation, design, and construction technique. Some of these buildings from the recent past are now listed buildings. This study centres on three construction projects under patented systems: Our Lady of "La Antigua", Orduña (Monier system), "La Ceres" flour mill, Bilbao (Hennebique system), and Alhóndiga, Bilbao (Blanc system). Preliminary structural studies analyzed morphology, reinforcements, concrete strength and pathological processes in each structure. Their results are compared with information taken from the patent systems in use at the time. This useful information on the structures, which may be expanded in future research, clearly describes the relationship between patent specifications and reality.